Factors Influencing Students' Difficulties in Using Formal Indonesian Language in The Campus Environment - Lubis, Fitriani; Nasution, Mutiara Akbar; Fitri, Anisa; Rizwinie, Khesya Sabilah; Sihaloho, Jhonathan; Pasaribu, Reyvanza Adliva Ananda; Salsabila, Salsabila; Siregar, Jihan Aulia (EDUCTUM: Journal Research, 2023)
The aim of this research is to identify the factors influencing students' difficulties in using formal Indonesian language in the campus environment. The Research Methodology employed in this study is a literature review method, examining and analyzing relevant literature or sources as research data. The findings of this research indicate that the factors affecting the difficulty of using formal language on campus involve internal and external factors, the influence of foreign cultures, globalization, and educational policies. Academic pressure, changes in communication culture, and shifts in education policies also play a role in creating these challenges for students.